Water use, transpiration, and crop coefficients for olives (cv. Cordovil), grown in orchards in Southern Portugal - Ramos, Alice (2009)
To improve the scheduling of irrigation for low-density olive trees (Olea europaea L.) grown in a typical Mediterranean environment of Southern Portugal, and to clarify the mechanisms of water uptake by trees, transpiration, soil water status and stomatal response to water deficit were measured in an olive orchard. Olive trees of cv. Cordovil were subject to three irrigation treatments: full-rate irrigation, sustained deficit irrigation (SDI) providing for approximately 60% of water applied at full-rate irrigation, and a regulated deficit irrigation (RDI) with water applied at periods during three critical phases: before-flowering, at beginning of pit-hardening, before crop-harvesting to replenish soil moisture to field capacity. There was also a dry-farming treatment. Trees responded differently to summer rainfall and irrigation water: full-rate irrigation, which received 880 mm of irrigation and 240 mm of rainfall, used 704 mm for transpiration; SDI, which received the same amount of rainfall and 448 mm of irrigation water, used 745 mm of water for transpiration; RDI, which received 69 mm of irrigation water and 240 mm of rainfall, used 638 mm of water for tree transpiration; dry-farming, which received no irrigation, benefited from 240 mm of summer and early autumn rain and used 404 mm of water for transpiration. The results support the hypothesis that trees under RDI and dry-farming satisfy most of their early atmospheric evaporative demand by extracting water from outside of the area wetted by drip irrigation. Scaled-up orchard transpiration was used to define orchard crop and water stress coefficients. With full-rate irrigation and SDI the results showed that during summer droughts olive trees slow down their physiological mechanisms to conserve water, regardless of amount applied. The derived crop coefficient results also indicated that SDI was the most appropriate for scheduling the irrigation of cv. Cordovil orchards in Southern Portugal although applying RDI helped sustain orchard transpiration and yields. Irrigation accounted for 11% of total water used in transpiration, with the balance extracted by roots in the large volume of soil lying in the areas between the trees. However, using the RDI scheme to schedule irrigation appears to be appropriate only in wet years with well distributed late summer rainfall or where there is a shortage of farm irrigation water. In general, and particularly in years with no summer and early autumn rains as can often occur in this region, the SDI regime appears to be more appropriate for scheduling irrigation.